Judgment of spatial orientation in patients with focal brain damage. Issue 5 (October 1971) - Renzi, Ennio De; Faglioni, Piero; Scotti, Giuseppe
Abstract : Thirty control and 121 brain-damaged patients with injury restricted to one hemisphere were presented with a test requiring the placing of a rod, fixed on a support by a hinged joint, in the same position as a model. Two versions of the test were given, one to be performed with the aid of vision and the other only by touch. The brain-damaged patients were subdivided into the following groups: right hemisphere patients without visual field defect (VFD): 30; right hemisphere patients with VFD: 20; left hemisphere patients without VFD: 46; left hemisphere patients with VFD: 25. The test modality did not differentially affect the performance of the groups. Both on the visually and on the tactually guided version of the test the right hemisphere group with VFD did significantly worse not only with respect to controls but also with respect to the three other braindamaged groups. The latter, in turn, were not significantly inferior to patients without cerebral damage. It appears, therefore, that when spatial perception is tested at a very basic and simple level, such as the detection of orientation in space of a rod, there is an almost complete dominance of the posterior region of the so-called minor hemisphere. This result must be contrasted with the less striking asymmetry of functions shown in more complex spatial tasks—for example, route finding, copying drawings, block designs—that are failed also by patients with damage to the left posterior area. Normal subjects reproduced the orientation of the rod on the horizontal plane with a constant error which was found to be dependent on the position of the model. Clockwise deviations were made when the model was on the left and counterclockwise deviations when the model was on the right. The constant error was present in left brain-damaged patients too, while it was not significantly different from zero in right brain-damaged patients. A systematic error was also found on the vertical plane and it consisted in the tendency to stop the rod below the level of the standard.